PERANCANGAN SISTEM INFORMASI KEHADIRAN ONLINE DENGAN MENGGUNAKAN QR CODE PADA FAKULTAS ILMU KOMPUTER UPN VETERAN JAKARTA - Yeremia Bonar Tambunan (2023)
The rapid advancement of Industrial Revolution 4.0 technology makes it easier for all stakeholders to collect and manage information for the needs of students, lecturers, and alumni in an academic environment. Attendance is a data collection activity that is used to determine student attendance in class. UPN Veteran Jakarta is currently conducting attendance activities using paper, which needs to be considered and reviewed regarding the use of paper to go green. In addition, the weakness of manual attendance is that fraud can occur between students, such as entrusting attendance. Therefore, we need a web-based student attendance system that can assist lecturers in managing and collecting attendance data so that it can be done quickly and efficiently. Making the attendance system can be done using the waterfall method by collecting data, system analysis, system design, and system implementation. This online attendance system is made using the Laravel framework and uses the PHP and MySQL programming languages for database management. The online attendance system was tested using black box testing to observe the input and output results of the software without knowing the code structure of the software. This test is carried out at the end of making the software to find out whether it can function properly.